PENGARUH TUNJANGAN KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BIMA - Rizki Zulyana; Khairul Amar (Jurnal Bina Bangsa Ekonomika, 2023)
The more aspects of the job that suit the individual's wishes, the higher the level of satisfaction felt. Aspects that can increase job satisfaction are the provision of work benefits and good work discipline. This research aims to determine the effect of work allowances and work discipline on employee job satisfaction at the Bima Regency Manpower and Transmigration Office. Associative type research using Likert scale questionnaire as a research instrument. The population used in this study was all employees at the Bima Regency Manpower and Transmigration Office as many as 111 respondents, the sample in this study was 55 employees who had civil servant status at the Bima Regency Manpower and Transmigration Office. The sampling technique is carried out by purposive sampling method. Data collection techniques use observation, questionnaires and literature studies. Data analysis techniques use validity tests, reliability tests, classical assumption tests and continue with multiple linear regression analysis, multiple correlation coefficients, determination tests, t tests and f tests. The results showed that work allowances and work discipline had a significant effect on employee job satisfaction at the Bima Regency Manpower and Transmigration Office